ANALISA PENGARUH CONSUMPTION VALUES DAN TRUST TERHADAP MINAT KONSUMEN UNTUK MEMBELI HEALTHY FAST FOOD - Muhammad Adlan Muhtadi (Ultima Management : Jurnal Ilmu Manajemen, 2022)
Abstract - The increase in fast food consumption in Indonesia is contrary to the changing lifestyle of Indonesian people who began to lead healthy lifestyles due to the outbreak of covid-19. However, there are positives from these circumstances that lead to business opportunities for the healthy food industry. FastFit is one of those fast food restaurants that offers low calorie fast food. However, the knowledge about FastFit is still lacking because the total search for FastFit keywords is still small. This can lead to low purchase interest because consumers tend to buy products from brands they know. This study aims to help FastFit to know what are the factors - factors seen by prospective consumers to choose healthy food products that will eventually lead to a buying interest in FastFit products. Research method in this research using conclusive research design with descriptive research method. Data analysis techniques use Structural Equation Model (SEM) which produces 4 out of 5 supporting hypotheses. The managerial implication that can be applied is to improve the quality and create a tester to prospective consumers. Keywords: Theory of Consumption Value; Trust; Purchase Intention; Healthy Fast Food